Effects of auriculotherapy on gestational hypertension: Randomized controlled trial study - Ladan Keshtkar; Fatemeh Ranjkesh; Mohammad Habibi; Farnoosh Rashvand (Wolters Kluwer Medknow Publications, 2024)
Background: This study aims to observe how auriculotherapy acts as a nonpharmacological treatment for pregnant women's gestational hypertension. Materials and Methods: This study was a randomized controlled trial. Eighty patients were with gestational hypertension recruited and divided into control (n = 40) and intervention (n = 40) groups. The control group just received the usual perinatal care. The intervention group received one month of auriculotherapy in addition to the usual care. Blood pressure was measured before and 15 minutes after rest in both groups twice a week. The data were analyzed using descriptive statistics and inferential tests. Results: The mean systolic blood pressure, based on the Mann-Whitney test, was not statistically significant between the two groups before the intervention and in the first two weeks after the intervention (p >0.05); however, after the third week of intervention, the mean systolic blood pressure in the intervention group was significantly lower than that in the control group (p <0.001). As per the Mann-Whitney test, the mean diastolic blood pressure was not statistically significant between the two groups before the intervention and the first week after the intervention (p <0.05). However, after the second week of intervention, the mean diastolic blood pressure in the intervention group was significantly lower than that in the control group, and this decrease was highest in the fourth week of the intervention (p <0.001). Conclusions: This study demonstrated that auriculotherapy would reduce blood pressure in pregnant women suffering from hypertension.